Adaptasi Dan Fenomena Culture Shock Pada Mahasiswa Pmm (Pertukaran Mahasiswa Mardeka Mandiri) Di Universitas Muhammadiyah Pringsewu - Putri Mega Utami (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2024)
Exchange students can be said to take place in an area that is temporary, moving and living in an unknown place, student concerns when each lifestyle is handled differently from culture shock to the culture of the new environment from the previous environment. Therefore, adjustments are needed to be able to adapt and communicate effectively with the surrounding community. Where cultural and environmental differences that will be faced include speech, behavior, language, food, weather and lifestyle. This research uses a qualitative research method with a phenomenological approach with data collection techniques carried out by interviewing 5 students from outside Lampung Province (Pringsewu). The results of this research show that the participants experienced 2 types of culture shock faced by students. First, language is the first inhibiting factor in communicating, language is important in effective communication, and participants barely understand and are not used to conversations using Javanese. This is because most of the Pringsewu community uses Javanese rather than Lampung. Second, the environment, which is the culture shock factor for PMM students, namely in terms of weather, time of day and the lifestyle of local residents. Adaptation efforts are made by increasing intense interaction, studying and understanding the language and culture of the local community. That way we can interact and relate to other people better, understand how they think and feel, and build better relationships. The ability to communicate effectively and understand an individual's culture and personality greatly influences the results which depend on each individual's competence.